Clavulanic Acid-Mediated Increases in Anterior Cingulate Glutamate Levels are Associated With Decreased Cocaine Craving and Brain Network Functional Connectivity Changes - Joya Maser, MS; Mary F. Morrison, MD; Helene Philogene Khalid, PhD; Ronan Cunningham; Daohai Yu, PhD; M. Ingre Walters, MD; Xiaoning Lu; Nicolas R. Bolo, PhD (Current Therapeutic Research)
Background: There is an urgent need for pharmacological treatment for cocaine (COC) use disorder (CUD). Glutamatergic transmission in the prefrontal cortex is affected by addictive behaviors. Clavulanic acid (CLAV), a glutamate transporter GLT-1 (excitatory amino acid transporter) activator, is a clinical-stage medication that has potential for treating CUD. Methods: In a pilot study, nine participants with CUD received 500 mg CLAV with dose escalations to 750 mg and 1000 mg over 10 days. In 5 separate magnetic resonance imaging (MRI) sessions, brain anterior cingulate cortex (ACC) glutamate level and resting state network (RSN) functional connectivity (FC) were assessed using MR spectroscopy and functional MRI. Craving was assessed at the same time points, between baseline (before CLAV), 6 days, and 10 days of CLAV. Independent component analysis with dual regression was used to identify RSN FC changes from baseline to Days 6 and 10. Relationships among glutamate, craving, and resting state FC values were analyzed. Results: Participants who achieved high ACC glutamate levels after CLAV treatment had robust decreases in COC craving (r = −0.90, P = 0.0009, n = 9). The salience network (SN) and executive control network (ECN) demonstrated an association between increased FC after CLAV treatment and low baseline ACC Glu levels (SN CLAV 750 mg, r = −0.82, P = 0.007) (ECN CLAV 1000 mg, r = −0.667, P = 0.050; n = 9). Conclusions: Glutamate associated changes in craving and FC of the salience and executive control brain networks support CLAV as a potentially efficacious pharmacological treatment for CUD.